Innovation Capabilities, Work Discipline, Leader Supervision and Their Effect On Employee Performance Pande Iron Crafts Center In Blitar Regency - Sonang Sitohang (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of innovation ability, work discipline, leadership supervision on the performance of Clushter Blacksmith employees in Blitar Regency. This research type is explanatory research with quantitative method. The population is permanent employees of Clushter Blacksmith, totaling 50 people with a complete enumeration sampling technique. Using a questionnaire to collect primary data related to innovation ability, work discipline, leadership supervision and employee performance. Data processing using Multiple Linear Regression Analysis with SPSS (Statissical Package for the Social Science) application. The results showed that innovation ability had a significant positive effect on the performance of the Blacksmithemployees performance in Blitar Regency. The higher the employee's innovation ability, the higher the employee's performance through the use of technology and information to develop, produce and market new products for the industry. Work discipline has a positive and significant effect on the performance of the Blacksmithemployees performance in Blitar Regency. The higher the employee's work discipline will have a good impact on employee performance. Supervision of the leadership has a positive and significant effect on the performance of the Blacksmithemployees performance in Blitar Regency. Supervision of the leadership is carried out to evaluate each employee's performance on a regular basis and provide input so that the performance of the employees develops.